High-damage-threshold hafnium oxide magnetron sputtering film for high-repetition-frequency femtosecond laser

Through the combination of etching pretreatment, magnetron sputtering technology and post-annealing treatment, high-quality hafnium dioxide films were prepared, which solved the problem of low damage threshold of existing high-frequency femtosecond laser optical films, and realized Film preparation with high damage threshold and excellent optical properties.

CN119465047APending Publication Date: 2025-02-18YANGTZE DELTA REGION INST OF UNIV OF ELECTRONICS SCI & TECH OF CHINE (HUZHOU)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310987451.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-08
Publication Date
2025-02-18

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a hafnium oxide magnetron sputtering film with a high damage threshold for high repetition frequency femtosecond laser. The invention discloses a preparation method of the hafnium oxide magnetron sputtering film with the high damage threshold for the high repetition frequency femtosecond laser. The preparation process comprises the following steps: 1, by taking fused quartz as a substrate, etching the fused quartz in a hydrofluoric acid buffer solution before coating, then immediately cleaning the substrate with acetone, ethanol and deionized water, and finally drying in a drying box; and 2, performing sputtering coating on the high-purity hafnium target material by adopting a radio frequency magnetron sputtering coating system, and regulating and controlling sputtering power and an oxygen / argon gas flow ratio in the sputtering process to obtain the hafnium dioxide film deposited on the fused quartz substrate. And 3, putting the film into an annealing furnace for high-temperature annealing to obtain the final hafnium dioxide film. The optical performance of the hafnium dioxide thin film is remarkably improved by combining pretreatment of the substrate, regulation and control of deposition parameters and treatment after annealing, and the hafnium dioxide thin film shows good transmissivity in an ultraviolet visible region and a high damage threshold value under high-repetition-frequency femtosecond laser irradiation and can be applied to the field of high-repetition-frequency femtosecond lasers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of femtosecond lasers and relates to a method for preparing a hafnium dioxide film for a high repetition rate femtosecond laser. Background Art

[0002] High repetition rate femtosecond lasers have a wide range of applications in surface processing, astrophysics, and additive manufacturing. Optical films used in laser systems play a vital role in guiding and transmitting laser beams. However, as laser power and repetition rate increase, the demand for optical films that can withstand extremely high power levels and repetition rates also increases proportionally. In order to ensure the reliable performance of high repetition rate femtosecond lasers, it is necessary to develop and manufacture optical films with high damage thresholds for high repetition rate femtosecond lasers. Studies have shown that the main reason for the low damage threshold of optical films is the defects in the substrate itself and the defects such as vacancies and gaps in the deposited films.

[0003] To date, various materials (oxides, chalcogenides, fluorides, etc.) have been widely used in the field of optical thin films to improve the laser transmission efficiency of lasers. However, chalcogenide and fluoride optical films reduce the environmental stability and mechanical stability of the system. In contrast, oxide films have become promising candidates due to their high melting point, excellent chemical and environmental stability, and relatively high laser-induced damage threshold. Among the many oxide films, hafnium dioxide films have many excellent properties such as good thermal stability, chemical stability, low light absorption and scattering, high transparency, and wide optical band gap. Therefore, they are widely used in the field of femtosecond lasers as anti-reflection films and anti-reflection films.

[0004] The performance of hafnium dioxide thin films mainly depends on the preparation method and deposition conditions of the film. At present, the main methods for preparing hafnium dioxide thin films are electron beam evaporation, atomic layer deposition and magnetron sputtering. The hafnium dioxide thin films prepared by electron beam evaporation have large laser scattering losses and poor thermal stability. Although atomic layer deposition technology can accurately control the composition and thickness of the film, its slow deposition rate and expensive precursor price limit the large-scale application of this technology in the field of laser thin films. In contrast, magnetron sputtering technology can produce uniform, well-adhesive and high-quality hafnium dioxide thin films. In addition, the dense films deposited by magnetron sputtering have high resistance to damage under femtosecond laser irradiation. In magnetron sputtering technology, sputtering power and oxygen / argon gas flow ratio have a huge impact on the microstructure, surface morphology, stoichiometric ratio and laser absorption of hafnium dioxide thin films. Thermal annealing is one of the most important post-treatment methods to improve the performance of deposited films. In the post-annealing process, the reasonable setting of annealing time and annealing temperature can optimize the defect density, microstructure and surface morphology of the film, thereby improving the laser-induced damage threshold of the optical film.

[0005] At present, there are few studies on the damage behavior of hafnium dioxide films under high repetition rate femtosecond laser irradiation, and the damage threshold of optical films used in the field of high repetition rate femtosecond laser is low. In view of the problems of poor substrate quality and film defects, the present invention adopts a method combining etching pretreatment, deposition parameter regulation and annealing post-treatment to prepare hafnium dioxide films with high damage threshold for high repetition rate femtosecond laser. Summary of the invention

[0006] The purpose of the present invention is to remove contaminants and polishing residues on the surface of a substrate based on etching pretreatment; combine the sputtering power and oxygen / argon gas flow ratio in magnetron sputtering technology to regulate the microstructure and stoichiometric ratio of the hafnium dioxide film, and prepare a hafnium dioxide optical film deposited on a fused quartz substrate; finally, the film is post-annealed to further reduce the defect size and density of the film, thereby improving the damage threshold under high repetition rate femtosecond laser irradiation.

[0007] To achieve this goal, the following technical solutions are applied:

[0008] Prepare a hydrofluoric acid buffer solution, and use the solution to etch the fused quartz substrate for pretreatment, then clean and dry it in acetone, ethanol and deionized water in turn. Use a high-purity hafnium target in the magnetron sputtering system, and pass an oxygen / argon mixed gas for sputtering. Finally, the deposited hafnium dioxide film is annealed for post-treatment. The specific process is as follows:

[0009] 1. Fused quartz substrate pretreatment:

[0010] Mix hydrofluoric acid, ammonium fluoride and deionized water in a certain mass ratio, stir them evenly with magnetic force at room temperature, and let them stand to obtain a hydrofluoric acid buffer solution. Use the prepared hydrofluoric acid buffer solution to etch the fused quartz substrate. Wash the etched substrate in acetone, anhydrous ethanol and deionized water in turn, and then dry it in a drying oven. The drying temperature is 45-100 °C and the drying time is 10-60 min.

[0011] 2. Preparation of hafnium dioxide film:

[0012] The cleaned substrate and high-purity hafnium target were installed in the magnetron sputtering system, and an oxygen / argon mixed gas was introduced in a certain ratio (flow ratio 1:3-1:1). At the same time, the sputtering power (100-500 W) was adjusted to prepare thin film samples under different deposition parameters.

[0013] 3. Post-annealing treatment of hafnium dioxide film:

[0014] The hafnium dioxide film deposited on the fused quartz substrate is placed in an annealing furnace, the annealing temperature is 300-500 ° C, the annealing time is 2-6 h, and the annealing atmosphere is air or oxygen.

[0015] 4. High repetition rate femtosecond laser damage threshold test:

[0016] The hafnium dioxide thin film deposited on a fused quartz substrate was tested for its damage threshold by a high repetition rate femtosecond laser with a repetition rate of 500 kHz. The test mode was S-on-1 [ISO Standard No.21254-2].

[0017] Furthermore, in step 1, the etching rate of the hydrofluoric acid buffer solution is 0.01 μm / min-0.05 μm / min, and the etching time is 5-30 min.

[0018] Furthermore, in step 2, the pressure of the vacuum chamber is reduced to 5×10 -4 Pa, after introducing gases with different flow ratios, the gas pressure rises to 1.2-2 Pa.

[0019] Furthermore, in step 2, the pure hafnium target is pre-sputtered for 5-10 min before coating.

[0020] Furthermore, during the coating in step 2, the temperature of the substrate is at room temperature without additional heating.

[0021] Furthermore, the heating rate during annealing in step 3 is 2-10 °C / min.

[0022] Further, in step 4, the wavelength of the femtosecond laser is set to 343 nm, 515 nm and 1030 nm. The focusing diameter of the laser beam is 1-10 μm.

[0023] Furthermore, in step 4, the femtosecond laser irradiation time is set to 1 s-10 s.

[0024] In summary, the beneficial effects of the present invention are as follows:

[0025] Pre-treatment of the fused quartz substrate with hydrofluoric acid etching can remove the surface contamination, redeposition layer and passivate surface defects of the fused quartz, thus obtaining a high-quality fused quartz substrate. Regulating and optimizing the deposition parameters of magnetron sputtering can obtain a wide optical bandgap hafnium dioxide film with a dense and smooth surface, uniform element distribution and stoichiometric ratio. Annealing post-treatment further reduces the defect size and defect density of the hafnium dioxide film, and improves the microstructure and surface morphology of the hafnium dioxide film. Finally, a hafnium dioxide film with low absorption, low scattering, high optical bandgap, high optical transmittance and high laser damage threshold is obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Scanning electron microscope images of the fused quartz substrate without etching and after pre-treatment with three different ratios of hydrofluoric acid buffer solution etching.

[0027] Figure 2 The X-ray diffraction pattern of the magnetron sputtering film prepared on the pretreated substrate and its annealed film indicates that the hafnium dioxide film was successfully prepared.

[0028] Figure 3 It is the damage threshold of the comparative example and the embodiment under high repetition rate femtosecond laser irradiation with the same parameters. Implementation

[0029] The present invention is further described below with reference to specific examples. It should be understood that the purpose of the examples is to further illustrate the content of the present invention, and they cannot be interpreted as limiting the protection scope of the present invention in any sense.

[0030] Comparative Example 1

[0031] The fused quartz substrate was cleaned in 50 ml acetone, anhydrous ethanol and deionized water for 10 min, and then dried in a drying oven at 55 °C for 60 min. The dried substrate was coated with a sputtering power of 200 W and an oxygen / argon gas flow ratio of 1 / 3.

[0032] Embodiment 1

[0033] Step 1: Weigh 1 g of hydrofluoric acid solution and 15 g of ammonium fluoride solution and dissolve them in 84 g of deionized water. Stir them magnetically at room temperature for 30 min, then place them for 2 h to obtain a hydrofluoric acid buffer solution, and etch the fused quartz substrate at a rate of 0.02 μm / min for 20 min. Then, wash the etched substrate in 50 ml of acetone, anhydrous ethanol, and deionized water for 10 min, and then dry it in a drying oven at 55 °C for 60 min. A high-quality fused quartz substrate is obtained.

[0034] Step 2: Install the fused quartz substrate and high-purity hafnium target in the magnetron sputtering machine, turn on the molecular pump, and obtain 5×10 -4 The vacuum degree of Pa was 2.0477 W. First, pre-sputtering was performed in a pure argon atmosphere with a sputtering power of 200 W for 10 min. Then, sputtering coating was performed for 2 h with a sputtering power of 200 W and an oxygen-argon flow ratio of 1 / 3. A hafnium dioxide film was obtained deposited on a fused quartz substrate.

[0035] Step 3: Place the hafnium dioxide film deposited on the fused quartz substrate obtained in step 2 into an annealing furnace for oxygen atmosphere annealing at a temperature of 400° C. for a time of 4 hours to obtain an annealed hafnium dioxide film.

[0036] Embodiment 2

[0037] Step 1: Weigh 2 g of hydrofluoric acid solution and 14 g of ammonium fluoride solution and dissolve them in 84 g of deionized water. Stir them magnetically at room temperature for 30 min, then place them for 2 h to obtain a hydrofluoric acid buffer solution, and etch the fused quartz substrate at a rate of 0.02 μm / min for 20 min. Then, wash the etched substrate in 50 ml of acetone, anhydrous ethanol, and deionized water for 10 min, and then dry it in a drying oven at 55 °C for 60 min. A high-quality fused quartz substrate is obtained.

[0038] Step 2: Install the fused quartz substrate and high-purity hafnium target in the magnetron sputtering machine, turn on the molecular pump, and obtain 5×10 -4 The vacuum degree of Pa was 2.0477 W. First, pre-sputtering was performed in a pure argon atmosphere with a sputtering power of 200 W for 10 min. Then, sputtering coating was performed for 2 h with a sputtering power of 200 W and an oxygen-argon flow ratio of 1 / 3. A hafnium dioxide film was obtained deposited on a fused quartz substrate.

[0039] Step 3: Place the hafnium dioxide film deposited on the fused quartz substrate obtained in step 2 into an annealing furnace for oxygen atmosphere annealing. The annealing temperature is 400 °C, and the annealing time is 4 h to obtain an annealed hafnium dioxide film.

[0040] Embodiment 3

[0041] Step 1: Weigh 1 g of hydrofluoric acid solution and 15 g of ammonium fluoride solution and dissolve them in 84 g of deionized water. Stir them magnetically at room temperature for 30 min, then place them for 2 h to obtain a hydrofluoric acid buffer solution, and etch the fused quartz substrate at a rate of 0.02 μm / min for 20 min. Then, wash the etched substrate in 50 ml of acetone, anhydrous ethanol, and deionized water for 10 min, and then dry it in a drying oven at 55 °C for 60 min. A high-quality fused quartz substrate is obtained.

[0042] Step 2: Install the fused quartz substrate and high-purity hafnium target in the magnetron sputtering machine, turn on the molecular pump, and obtain 5×10 -4 The vacuum degree of Pa was 2.0477 W. First, pre-sputtering was performed in a pure argon atmosphere with a sputtering power of 200 W for 10 min. Then, sputtering coating was performed for 2 h with a sputtering power of 400 W and an oxygen-argon flow ratio of 1 / 3. A hafnium dioxide film was obtained deposited on a fused quartz substrate.

[0043] Step 3: Place the hafnium dioxide film deposited on the fused quartz substrate obtained in step 2 into an annealing furnace for oxygen atmosphere annealing. The annealing temperature is 400 °C, and the annealing time is 4 h to obtain an annealed hafnium dioxide film.

[0044] Embodiment 4

[0045] Step 1: Weigh 1 g of hydrofluoric acid solution and 15 g of ammonium fluoride solution and dissolve them in 84 g of deionized water. Stir them magnetically at room temperature for 30 min, then place them for 2 h to obtain a hydrofluoric acid buffer solution, and etch the fused quartz substrate at a rate of 0.02 μm / min for 20 min. Then, wash the etched substrate in 50 ml of acetone, anhydrous ethanol, and deionized water for 10 min, and then dry it in a drying oven at 55 °C for 60 min. A high-quality fused quartz substrate is obtained.

[0046] Step 2: Install the fused quartz substrate and high-purity hafnium target in the magnetron sputtering machine, turn on the molecular pump, and obtain 5×10 -4 The vacuum degree of Pa was 2.0477 W. First, pre-sputtering was performed in a pure argon atmosphere with a sputtering power of 200 W for 10 min. Then, sputtering coating was performed for 2 h with a sputtering power of 400 W and an oxygen-argon flow ratio of 1 / 3. A hafnium dioxide film was obtained deposited on a fused quartz substrate.

[0047] Step 3: Place the hafnium dioxide film deposited on the fused quartz substrate obtained in step 2 into an annealing furnace for oxygen atmosphere annealing. The annealing temperature is 600 °C, and the annealing time is 4 h to obtain an annealed hafnium dioxide film.

[0048] The above embodiments are only used to explain the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of protection of the present application. It should be pointed out that for ordinary technicians in this field, any modifications and changes made to the present invention without departing from the technical solution concept of the present application belong to the scope of protection of the present application.

Claims

1. A high damage threshold hafnium dioxide magnetron sputtering film for high repetition rate femtosecond laser, characterized in that: The method has the following preparation steps: (1) Fused quartz is used as the substrate for coating. Before coating, hydrofluoric acid buffer solution is prepared with different proportions of hydrofluoric acid, ammonium fluoride and deionized water, and the fused quartz substrate is pre-etched. The etched substrate is cleaned with acetone, ethanol and deionized water, and finally dried in a drying oven; (2) Using a radio frequency magnetron sputtering coating system, a high-purity hafnium target material is used for sputtering coating. During the sputtering process, the sputtering power and the oxygen / argon gas flow ratio are adjusted to obtain a hafnium dioxide film deposited on a fused quartz substrate; (3) placing the prepared hafnium dioxide film into an annealing furnace for high-temperature annealing treatment, adjusting the annealing time and annealing temperature, and obtaining a final hafnium dioxide film.

2. The method for preparing a high damage threshold hafnium dioxide magnetron sputtering film for high repetition rate femtosecond laser according to claim 1, characterized in that: The hydrofluoric acid content of the hydrofluoric acid buffer solution in step (1) is 0.5%-2%, and the etching time is 5-30 min; the drying temperature is 45-100 °C, and the drying time is 10-60 min.

3. The method for preparing a high damage threshold hafnium dioxide magnetron sputtering film for high repetition rate femtosecond laser according to claim 1, characterized in that: The sputtering power in step (2) is adjustable in the range of 100-500 W, and the oxygen / argon gas flow ratio is set to 1:3-1:

1.

4. The method for preparing a high damage threshold hafnium dioxide magnetron sputtering film for high repetition rate femtosecond laser according to claim 1, characterized in that: In step (3), the annealing temperature is 300-500°C, the annealing time is 2-6 h, and the annealing atmosphere is air or oxygen.

5. A hafnium dioxide magnetron sputtering film for high repetition rate femtosecond laser prepared as claimed in claim 1 has a high damage threshold under high repetition rate femtosecond laser irradiation, and exhibits excellent transmittance in the range of 300-800 nm, as well as low laser absorption and laser scattering.